Intraradicular fiberglass posts: comparison among different techniques for restoring flared roots (Research, Society and Development, 2022)
This in vitro study aimed to analyze the fracture strength and failure pattern of flared bovine roots restored with different intraradicular fiber posts and core materials, without a ferrule. To conduct this study fifty bovine incisor roots were treated endodontically, and divided into five groups (n=10), according to the following fiber post techniques and core materials: prefabricated fiberglass post and full-body bulk-fill resin composite (PF-BF); prefabricated fiberglass post and dual function resin cement (PF-RC); direct anatomic post and full-body bulk-fill resin composite (AP-BF); CAD-CAM integrated fiberglass post-and-core (CAD-PC); and adjustable fiberglass post and full-body bulk-fill resin composite (AD-BF). Intraradicular fiber posts were cemented with dual functional resin cement (Allcem Core, FGM), restored with CAD-CAM composite crowns (Brava, FGM), and subjected to loading. The data were analyzed by generalized linear models (p